Innovation Activities in EU Service Industries - Kamil DECYK (Communications of International Proceedings, 2024)
The aim of the analyzes was to characterize and estimate innovation activities at the level of service industries in EU countries. In the course of the research carried out, the research hypothesis was verified, which assumed that: the highest level of innovation activity in the EU services sector was characterized by the following industries: information and communication (J) and professional, scientific and technical activities (M), classified as high-tech knowledge-intensive services sector. The following methods/techniques/research tools were used to achieve the goal and verify the research hypothesis: literature analysis at the international level, comparative and indicator analysis using tools in the field of descriptive statistics. In the course of the analyses, the hypothesis was positively verified, but only in the part concerning industry J. In the case of section M, there were positive symptoms of innovation activity, but it was generally at a lower level than, for example, in section financial and insurance activities (K). Based on the results obtained, it was noted that, in general, the highest level of innovativeness was characterized by industry J, and the lowest – by transportation and storage (H). Entities representing all analyzed industries were generally active in innovation, more in the field of business process innovation than product innovation, specifically in the sphere of innovations related to new or improved methods for information processing or communication. Product innovations were dominated by services, not products. Product innovations were characterized by a higher level of innovativeness in only two industries: J and M. In the future, special attention should be paid to the support of the M section, which should be of a continuous and systemic nature, due to the direct role of this industry in the process of creating the level of innovativeness of the entire EU.
Keywords: innovation; EU countries; services sector; high-tech knowledge-intensive services sector